Application of teaching strategies in grade 12 english second language classrooms in Mankweng Circuit, Limpopo Province - Choshi, Morongwa Adolphina (My University, 2015)
The purpose of this study is to investigate the application of teaching strategies in Grade 12 English Second language in Mankweng Circuit, Limpopo Province. This study aims to achieve the following objectives: to identify teaching strategies used in Grade 12 English second language classrooms in Mankweng Circuit, Limpopo Province, to assess teachers experiences in applying a variety of teaching strategies in English second language classrooms, to establish if the way in which English second language teachers are trained affect the way they teach and to determine how teaching strategies affect the performance of learners in English second language classrooms. The study applied a mixed method-quantitative and qualitative approaches to elicit data. An exploratory research was applied to explain teaching strategies. The literature review was carried out focusing on the following themes: Communicative language teaching model, Language needs for English Second language teaching and teaching strategies in English Second language. In addition, the study found the following: there are no prescribed teaching strategies by the Department of Basic Education, teachers are innovative in coming up with teaching strategies that suit the lesson and the type of learners, learners learn English better when teachers apply various teaching strategies during lessons and teachers who apply teaching strategies in Grade 12 English Second language classrooms contribute to learners good performance in all schools at Mankweng Circuit. Lastly, the study recommend that teachers of English in Grade 12 classes in Mankweng Circuit should be made aware that teaching strategies are important and should be applied at all times during the lessons, all teachers who teach English Second language in all grades, Grade R- 12 should apply teaching strategies as they contribute to the learners understanding of the subject, etc.
Thesis (M. A. (English Studies)) -- University of Limpopo, 2015
Keywords: English second language; Teaching strategies; English language -- Study and teaching -- South Africa -- Limpopo; Second language acquisition; English language -- Study and teaching -- Foreign speakers; Teaching